Obszary poradnictwa i wsparcia społecznego w aspekcie poprawy zatrudnialności absolwentów szkół zawodowych - Jeruszka , Urszula (Studia Edukacyjne, 2017)
The text “Counseling and Social Support as Improving the Employability of Graduates of Vocational Schools” focuses on showing the causes of the low employability of graduates of vocational schools and the ways to help and support instruments for the graduates’ successful entry into the labor market. This article interprets concepts of absolute and relative employability as well as learned helplessness on the labor market, which points to the need for differentiation. The text looks at the fate of professional graduate studies as a source of information about the demand for support activities – career counseling and social support. The text moreover indicates problems corresponding not only to events occurring at one point in a person’s life, but also the processes influencing the growth of the portion of the human capital related to education. Support measures are considered in relation to decisions affecting the educational path and professional graduate (prevention) and therefore the school-induced competence of entering the labor market (prevention of the negative consequences of differences between learning outcomes and employers’ expectations).